Cardiac Autonomic Control Mechanisms in the Pathogenesis of Chagas' Heart Disease - Dávila, Diego F.; Donis, Jose H.; Arata de Bellabarba, Gabriela; Villarroel, Vanesa; Sanchez, Francisco; Berrueta, Lisbeth; Salmen, Siham; Das Neves, Barbara (Interdisciplinary Perspectives on Infectious Diseases, 2012)
Primary abnormalities of the autonomic nervous system had been postulated as the pathogenic mechanisms of myocardial damage, in patients with Chagas disease. However, recent investigations indicate that these abnormalities are secondary and amenable to treatment with beta-adrenergic blockers. Moreover, muscarinic cardiac autoantibodies appear to enhance parasympathetic activity on the sinus node. Therefore, the purpose of this paper is to analyze how knowledge on Chagas' disease evolved from being initially considered as a primary cardioneuromyopathy to the current status of a congestive cardiomyopathy of parasitic origin.